Big impact? The meaning and impact of Big Data in information management / Tengku Adil Tengku Izhar - Tengku Izhar, Tengku Adil (Faculty of Information Management, 2015)
Big Data is a new way of thinking about enterprise data and how it can drive business value. The amount of data that is available to businesses is increasing, with social media and machine-to-machine as just two of the leading sources. The central role of business services in today's enterprises, and the more complex architecture through which they are delivered, make it important to manage Big Data solutions from a business perspective. Business perspective focuses on business objectives and benefit, and prioritizes resources and activities according to the needs of the business. In this way, effective evaluation of the Big Data can ensure optimal relevance of data for more effective decision-making to support the business goals.